SISTEM RELIGI DAN UPACARA KEAGAMAAN MASYARAKAT BADUY LUAR - Halimah, Siti; Sapriya; Encep Supriatna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Baduy community is one of the traditional groups in Indonesia which still maintains its traditions and customs. Divided into two large groups, namely Inner Baduy and Outer Baduy, this community has a religious and ritual system that is an integral part of their lives. This religious system is rooted in the Sundanese Wiwitan belief which teaches harmony with nature, respect for ancestors and devotion to the Creator. Ceremonies such as Seba Baduy, Kawalu, Ngaruat, and Seren Taun become media for expressing the spiritual, social, and ecological values ​​of the Outer Baduy community. This article aims to describe the religious system and religious ceremonies of the Outer Baduy community based on recent studies, with a focus on philosophical values ​​and their relevance in modern life. This research uses a qualitative approach based on literature studies from various scientific sources in 2022-2024. The research results show that the traditions and rituals of the Outer Baduy community are not only cultural heritage but also contribute to the preservation of universal values ​​that are relevant to the challenges of the times.